Improving the Eighth Grade Students’ Listening Comprehension Achievement by using Dictation Techniques - Abd. Syakur (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
Dictation is an ancient technique in teaching language becoming one of interesting ways to improve the students’ listening comprehension proposed by Davis and Involucres (1988). This study was aimed to solve the students’ listening comprehension achievement by using dictation techniques as a technique in teaching listening at SMP Al-falah Surabaya in the academic year 2019/2020. Classroom Action Research (CAR) was applied in this study in two cycles. In this classroom action research, the technique was divided into note taking and partial dictation/cloze dictation. The primary data about students listening achievement were gained from the listening test. Meanwhile, the supporting data were gathered from observation and documentation. The results on students’ activity showed the use of text dictation techniques could improve the eighth-grade students’ activity in listening. Furthermore, In the first cycle of the test’ result, the teaching listening activity was not so good as what was expected. On the average, the percentage of the students’ involvement in the process of teaching listening was only 45% in the first meeting and 50% in the second meeting. But, in the second cycle the percentage of students’ involvement in the process of teaching listening increased from 77% in the first meeting to 80% in the second meeting. This improvement happened because of some revision, they were; choosing the text with familiar story for the students, reading the text more clearly, turning up the volume, and using more gestures in teaching listening technique.